2023
DOI: 10.1039/d3dd00033h
|View full text |Cite
|
Sign up to set email alerts
|

A high-throughput workflow for the synthesis of CdSe nanocrystals using a sonochemical materials acceleration platform

Abstract: A sonochemical Materials Acceleration Platform was implemented to synthesize CdSe nanocrystals under 625 unique conditions (in triplicate) in less than 6 weeks. The modularity of the workflow is adaptable to a variety of applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…New tools can support a host of different experiments. For example, a variety of probes can be immersed in media using the same Jubilee tool as our inoculation loop; a sonicator tool has been elsewhere integrated into high-throughput workflows using Jubilee [ 45 ]. Augmented deck attachments can provide heating, cooling, and stirring capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…New tools can support a host of different experiments. For example, a variety of probes can be immersed in media using the same Jubilee tool as our inoculation loop; a sonicator tool has been elsewhere integrated into high-throughput workflows using Jubilee [ 45 ]. Augmented deck attachments can provide heating, cooling, and stirring capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Sidekick liquid dispenser 94 was designed around the liquid dispensing requirements associated with automated exploratory synthesis of halide perovskites, 99 and only later used for teaching an introductory chemistry laboratory on automation. 100 Similarly, the Jubilee system 59 was originally demonstrated in the context of nanocrystal synthesis research, 101 and later used for education. 60…”
Section: How Are Frugal Twins Being Used In Education and Research?mentioning
confidence: 99%
“…8a). 60 Politi et al 59 have demonstrated the use of this versatile, multi-tool platform configured for automated ultrasound application (Fig. 8c), along with an Opentrons OT-2 liquid-handling robot and a well-plate spectrometer for the synthesis of CdSe nanocrystals.…”
Section: How Are Frugal Twins Being Used In Education and Research?mentioning
confidence: 99%
See 2 more Smart Citations